Pemberdayaan Masyarakat Desa Limehu dalam Mengelola Lingkungan Menuju Desa Pelangi - Meylan Saleh; Evi Hasim (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2021)
The disasters that occurred in Indonesia, including in the Gorontalo region, were not only deforestation, but the waste problem became a complicated and difficult problem to deal with. Public awareness of the importance of keeping the environment clean is still low. The imbalance in the structure and function of the material cycle occurs due to natural processes or human actions. Flood disaster is one of human activities, including throwing garbage in any place. Therefore, a strategic approach in waste management is needed. The location of Limehu village is also included in a flood-prone area, so this village requires many activities that can reduce the impact of flooding. One of the activities that will be carried out is recycling household waste in the form of used towels/carpets which are transformed into beautiful and simple flower pots. Key words: environment, empowerment, flower pots,